Evaluation of the results of treatment of kidney recipients at the outpatient stage against the background of minimizing immunosuppressive therapy - E. V. Parabina; O. V. Fatenkov; M. N. Myakotnykh; A. A. Mironov; A. G. Dodonov (Лечащий Врач, 2023)
Objective. To study the effect of immunosuppressive therapy based on a reduction in standard dosages and target values of tacrolimus concentrations on the results of the postoperative period in recipients with a transplanted kidney. Materials and methods. The study included 176 kidney recipients who are under outpatient supervision of a nephrologist at the Samara Center for Organ and Tissue Transplantation. In accordance with the purpose and objectives of the study, the recipients were divided into two groups. The first group (control) included 78 patients receiving standard immunosuppressive therapy with calcineurin inhibitors (tacrolimus prolonged action) in combination with standard dosages of mycophenolic acid. The target concentration of tacrolimus in this group was 7-8 ng/ml. The second group (the main one) included 98 patients who received immunosuppressive therapy according to the tacrolimus prolonged action scheme in reduced dosages in combination with mycophenolic acid. The target concentration of tacrolimus in this group was 5-6 ng/ml. Both groups were comparable by gender, age, type and duration of stay on renal replacement therapy, as well as by the main diagnosis that led to chronic kidney disease.Results. In the course of the study, it was revealed that the minimization of IST leads to an improvement in the long-term results of transplantation. In the late postoperative period, in the group with reduced doses and target values of tacrolimus concentration, the creatinine level remained significantly lower than in the control subgroup. There was also a significant difference in the glomerular filtration rate – in the study group it was significantly higher by 20% than in the control group. A decrease in the target concentrations of tacrolimus in the postoperative period significantly led to a decrease in the frequency of dose-dependent side effects, which subsequently led to a significant improvement in the quality of life of recipients in the control group.